2017
DOI: 10.1111/gcb.13618
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in agricultural soils: drivers of its distribution at the global scale

Abstract: Phosphorus (P) availability in soils limits crop yields in many regions of the World, while excess of soil P triggers aquatic eutrophication in other regions. Numerous processes drive the global spatial distribution of P in agricultural soils, but their relative roles remain unclear. Here, we combined several global data sets describing these drivers with a soil P dynamics model to simulate the distribution of P in agricultural soils and to assess the contributions of the different drivers at the global scale.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 53 publications
6
137
0
Order By: Relevance
“…The P tot /P in ratio estimated in this study falls in the middle of the range of previous studies going from between 2.8% and 23% (Table 2). A similar CV was reported by Ringeval et al (2017) in modeling farm P inputs and outputs with a global Figure 5. A similar CV was reported by Ringeval et al (2017) in modeling farm P inputs and outputs with a global Figure 5.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The P tot /P in ratio estimated in this study falls in the middle of the range of previous studies going from between 2.8% and 23% (Table 2). A similar CV was reported by Ringeval et al (2017) in modeling farm P inputs and outputs with a global Figure 5. A similar CV was reported by Ringeval et al (2017) in modeling farm P inputs and outputs with a global Figure 5.…”
Section: Discussionsupporting
confidence: 81%
“…This necessitates considering plant-soil-management as a coupled system. However, P losses and fertilizer requirements vary substantially among different crops (Ringeval et al, 2017). Liu et al, 2008;Quinton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A simplified two-pool (labile and stable pools) P model, the Dynamic Phosphorus Pool Simulator (DPPS), has been developed to estimate P legacies from regional to global scales (Lun et al, 2018;Mogollón et al, 2018;Zhang et al, 2017). Other researchers used soil P dynamics models with more than two P pools (Goll et al, 2012;Ringeval et al, 2017;Wang et al, 2009;Yang et al, 2013) to study the distribution of soil P. Due to lack of data and understanding, it is difficult to compare and validate soil P pool estimates from different models.…”
Section: 1029/2018gb006060mentioning
confidence: 99%
“…Since the crop P demand is calculated from the ORCHIDEE‐CROP biomass pools in irrigated conditions, the climate determines the yield potential and subsequently the distribution shape. For potential root P uptake, we have shown that 80% of the spatial variability is explained by the P ILAB distribution (section 3.1), which in turn depends mostly on the historical farm input/output balance and soil biogeochemical background (Ringeval et al, ).…”
Section: Resultsmentioning
confidence: 97%
“…Because the potential P uptake is common to all crops/methods, this points to the uptake as the main determinant of the yield gap uncertainty. Since the uncertainty in the potential root P uptake is largely explained by P ILAB (Figure , bottom), this uncertainty can be traced back to the uncertainty of the main drivers in the P ILAB pool, which are the history of farm inputs/outputs and the soil biogeochemical background (Ringeval et al, ). For rice, there is a notable difference between the three limitation methods (Figure , top right) that is due to differences between the methods to estimate the demand (as explained in section 3.2).…”
Section: Resultsmentioning
confidence: 99%